Acute and chronic effects of cold treatment on physiological variables and neuromuscular function during a short training period in men - Karvinen, Susanna (2015)
Introduction. Recovery following various physical exercises is a complicated process. The exercise session can involve strong demands on both muscle structure and energy production (aerobic and anaerobic). Many exercise sessions also induce muscle damage (exercise induced muscle damage; EIMD). Different recovery methods attempt to alleviate or prevent EIMD and its associated symptoms, such as muscle soreness and swelling, and reduction in muscle function. One of the used strategies is cold treatment (cryotherapy), which decreases tissue temperature and subsequently effects on e.g. blood flow, metabolism and neural conductance velocity. To date, there is conflicting evidence to support the use of cryotherapy following a single exercise, and only few studies have examined the effect of it over a longer time period. Thus, the aim of this study was to assess the effects of cryotherapy on recovery and on the amount of EIMD both after an anaerobic running exercise and over a weeklong training period. Moreover, a recently developed cooling technique called cold mist shower (Amandan®, Amandan Healthcare Oy Ltd., www.amandan.fi, Finland, 2015) was tested. Methods. A total of eight male subjects (age 22.9 ± 1.4 years, height 1.77 ± 0.06 m, weight 79.1 ± 7.6 kg, and fat percentage 13.3 ± 2.9 %) participated in the study, which consisted of an acute phase of 48 h and a weeklong training period. All subjects completed the study protocol both with (COLD) and without (CONTROL) cryotherapy (2 min at 10–15°C) in a random order. The acute responses were measured after an anaerobic running (10 x 20 m shuttle running twice, with a 3 min break). Cryotherapy was applied immediately, and 12, 24 and 36 h after the running exercise. The training period consisted of three hypertrophic strength training sessions and three anaerobic interval running sessions on alternating days, and cryotherapy was applied once after every training session. Muscle damage (myoglobin, creatine kinase, CK), inflammation (C-reactive protein), endocrine responses (testosterone, SHBG and cortisol) and perception of muscle soreness (DOMS) were measured before (Pre) and immediately (0 min), 30 min, 60 min, 24 h and 48 h after the running exercise, and 4 d after the training period (Post). Anaerobic metabolism (lactate) was evaluated at Pre, 0, 30 and 60 min. Maximal voluntary isometric force of the knee extensors, jumping ability (a countermovement jump), and 10 x 20 m maximal sprint running were evaluated at Pre, 48 h and Post. Results. The intensive anaerobic running exercise (peak blood lactate in CONTROL 16.3 ± 3.6 vs. in COLD 16.2 ± 3.4 mmol/l) induced a small increase in DOMS, myoglobin and CK levels in both groups, and there were no differences between the groups (P > 0.05). Following the training period, myoglobin concentration was significantly (P < 0.05) lower in COLD compared to CONTROL (COLD 24.64 ± 5.63 ng/ml vs. CONTROL 36.35 ± 14.02 ng/ml). In COLD, the Post-value was also significantly (P < 0.05) lower compared to the Pre-value both in myoglobin (Pre 29.95 ± 6.90 ng/ml vs. Post 24.64 ± 5.63 ng/ml) and in CK (Pre 251.00 ± 143.83 U/l vs. Post 168.13 ± 91.90 U/l). In physical performance variables there were no significant differences between the groups. Conclusion. The finding in myoglobin provides some evidence that the cold mist shower might decrease the amount of EIMD over a weeklong training period. However, no cold mist effects on the acute recovery after anaerobic running exercise were observed.